Regulation of Th1 T Cell Differentiation by Iron via Upregulation of T Cell Immunoglobulin and Mucin Containing Protein-3 (TIM-3) - Pfeifhofer-Obermair, Christa; Tymoszuk, Piotr; Nairz, Manfred; Schroll, Andrea; Klais, Gloria; Demetz, Egon; Engl, Sabine; Brigo, Natascha; Weiss, Günter (Frontiers in Immunology, 2021)
Iron plays an important role in host–pathogen interactions, in being an essential element for both pathogen and host metabolism, but also by impacting immune cell differentiation and anti-microbial effector pathways. Iron has been implicated to affect the differentiation of T lymphocytes during inflammation, however, so far the underlying mechanism remained elusive. In order to study the role of iron in T cell differentiation we here investigated how dietary iron supplementation affects T cell function and outcome in a model of chronic infection with the intracellular bacterium Salmonella enterica serovar typhimurium (S. Typhimurium). Iron loading prior to infection fostered bacterial burden and, unexpectedly, reduced differentiation of CD4+ T helper cells type 1 (Th1) and expression of interferon-gamma (IFNγ), a key cytokine to control infections with intracellular pathogens. This effect could be traced back to iron-mediated induction of the negative immune checkpoint regulator T cell immunoglobulin and mucin domain-containing protein 3 (TIM-3), expressed on the surface of this T cell subset. In vitro experiments demonstrated that iron supplementation specifically upregulated mRNA and protein expression of TIM-3 in naïve Th cells in a dose-depdendent manner and hindered priming of those T cells towards Th1 differentiation. Importantly, administration of TIM-3 blocking antibodies to iron-loaded mice infected with S. Typhimurium virtually restored Th1 cell differentiation and significantly improved bacterial control. Our data uncover a novel mechanism by which iron modulates CD4+ cell differentiation and functionality and hence impacts infection control with intracellular pathogens. Specifically, iron inhibits the differentiation of naive CD4+ T cells to protective IFNγ producing Th1 lymphocytes via stimulation of TIM-3 expression. Finally, TIM-3 may serve as a novel drug target for the treatment of chronic infections with intracellular pathogens, specifically in iron loading diseases.